Ductile-brittle transition temperature of polylactic acid-based biocomposite - Kaiser, Mohammad Rejaul; Anuar, Hazleen; Razak, S.B.A. (Sage Publications, 2013)
Almost all materials exhibit sensitivity of mechanical properties to temperature. Polylactic acid (PLA), an amorphous polymeric material, also exhibits this type of behavior. Because of its limited application in structural purpose, very few journals and articles study the ductile–brittle transition temperature (DBTT) of polymeric materials, especially PLA. It is necessary to determine DBTT to avoid brittle and catastrophic failure. This article determined the ductile-to-brittle transition of various PLA-based biocomposite. A comprehensive database was developed to determine the DBTT of PLA, PLA-20KF, PLA-20KF-5Clay, and PLA-5Clay. Impact tests were carried out on unnotched standard specimens at temperatures ranging from -5°C to 28°C. The result shows that higher percentage of filler namely PLA-20KF and PLA-20KF-5Clay show lower impact strength and no significant decrease in impact strength with temperature. In contrast, lower percentage of filler such as PLA and PLA-5Clay shows better impact strength and comparatively sharp decrease in impact strength with temperature. Dynamic mechanical analysis (DMA) and fractographic analysis confirmed these statements that brittle fracture was observed in higher percentage of filled biocomposites whereas comparatively ductile fracture in lower percentage of filled biocomposites.